2011
DOI: 10.1111/j.1533-8525.2011.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalizing Social Movements: The Dual Strategy of the Korean Women's Movement

Abstract: Since the 1990s, scholars have paid attention to the role of social movements traversing the official terrain of politics by blending a "contention" strategy with an "engagement" strategy. The literature often highlights the contribution of institutionalized social movements to policymaking and sociopolitical change, but rarely addresses why and how specific social movement organizations gain routine access to formal politics. Using the Korean women's movement as a case study, I analyze the conditions for move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 39 publications
0
25
0
4
Order By: Relevance
“…150-151). Especially when their representatives start acting as members of governments and taking positions in official administrative structures, this process has attracted the attention of many scholars (Giugni & Passy, 1998;Goldstone, 2004;Oommen, 1990;Santoro & McGuire, 1997;Suh, 2011). These works seek especially to understand the effects of this relation in two ways.…”
Section: The Institu Tionaliz Ation Of So Cial Movement S and C O-optionmentioning
confidence: 99%
See 1 more Smart Citation
“…150-151). Especially when their representatives start acting as members of governments and taking positions in official administrative structures, this process has attracted the attention of many scholars (Giugni & Passy, 1998;Goldstone, 2004;Oommen, 1990;Santoro & McGuire, 1997;Suh, 2011). These works seek especially to understand the effects of this relation in two ways.…”
Section: The Institu Tionaliz Ation Of So Cial Movement S and C O-optionmentioning
confidence: 99%
“…Nevertheless, recent studies have shown different paths taken by different groups and social contexts. In many countries some movements have been acting not only cooperatively with formal social institutions, but there is also a growing process of professionalization and bureaucratization of their structures (Giugni & Passy, 1998;Goldstone, 2004;Oommen, 1990;Santoro & McGuire, 1997;Suh, 2011). Consequently, the adoption of strategies of moderate action and participation in the bureaucratic apparatus of the state also subvert the basis of the traditional analysis on these movements.…”
Section: The Institu Tionaliz Ation Of So Cial Movement S and C O-optionmentioning
confidence: 99%
“…For instance, Launsbury (: 94) suggests focusing on the fracture lines of institutions in order to understand the possibilities for ongoing change within these structures. Suh (: 444) proposes moving beyond an identification of institutionalization with co‐option, arguing that this structured process of movements “does not always entail the risk of de‐radicalization, de‐politization, or de‐mobilization of collective action”. This more open‐ended approach seems suitable for analyzing how Afro‐Venezuelan organizations strategically pursue institutionalization within the Venezuelan state as a response to their lack of ethnic recognition within the national constitution.…”
Section: Venezuelan Social Movements and The State: Beyond Traditionamentioning
confidence: 99%
“…This means that social movements can achieve their goals by becoming more professional, hierarchal, and cooperating closely with authorities such as political parties, international organizations, or state bureaucracies (Banaszak 2010;Costain 1981;Giugni and Passy 1998;Gusfield 1955;Meyer 2007;Ruzza 1997;Seippel 2001;Suh 2011;Zald et al 2005). For example, Staggenborg (1988) showed how the pro-choice movement in the United States created new opportunities for influencing policy change via institutionalization.…”
Section: Previous Work On Social Movements and Institutional Changementioning
confidence: 99%